Generation of long-lived charges in organic semiconductor heterojunction nanoparticles for efficient photocatalytic hydrogen evolution - Kosco, J; Gonzalez-Carrero, S; Howells, CT; Fei, T; Dong, Y; Sougrat, R; Harrison, GT; Firdaus, Y; Sheelamanthula, R; Purushothaman, B; Moruzzi, F; Xu, W; et al. (Springer Nature, 2022)
Organic semiconductor photocatalysts for the production of solar fuels are attractive as they can be synthetically tuned to absorb visible light while simultaneously retaining suitable energy levels to drive a range of processes. However, a greater understanding of the photophysics that determines the function of organic semiconductor heterojunction nanoparticles is needed to optimize performance. Here, we show that such materials can intrinsically generate remarkably long-lived reactive charges, enabling them to efficiently drive sacrificial hydrogen evolution. Our optimized hetereojunction photocatalysts comprise the conjugated polymer PM6 matched with Y6 or PCBM electron acceptors, and achieve external quantum efficiencies of 1.0% to 5.0% at 400 to 900 nm and 8.7% to 2.6% at 400 to 700 nm, respectively. Employing transient and operando spectroscopies, we find that the heterojunction structure in these nanoparticles greatly enhances the generation of long-lived charges (millisecond to second timescale) even in the absence of electron/hole scavengers or Pt. Such long-lived reactive charges open potential applications in water-splitting Z-schemes and in driving kinetically slow and technologically desirable oxidations.